Design and validation of a lower limb exoskeleton employing the recumbent cycling modality for post-stroke rehabilitation. (December 2014) - Yan, Hua; Yang, Canjun
This paper presents the design and validation of a lower limb exoskeleton robot for post-stroke patients at the early stage of neurorehabilitation. Instead of the usual walking gait, the popular exercise, recumbent cycling, is adopted to provide a safe and comfortable movement training to the patients who lost active motor abilities due to a very low muscle power. The exoskeleton robot mounted on a commercial wheelchair possesses two pairs of hip and knee joints on the right and left legs, respectively, and each joint has one degree of freedom actuated by a custom-made linear actuator in the sagittal plane. Additionally, two passive ankle joints are added to provide a limited range of motion for human comfort. The hip and knee joint motion profiles were calculated based on a simplified kinematic model of the recumbent cycling modality, and implemented through the motor position–velocity–time trajectory. Clinical trials were conducted on six stable post-stroke patients with a low muscle power under the supervision of a skilled therapist. The preliminary results validated the functionality and feasibility of the new exoskeleton robot and showed a promising application of the recumbent cycling modality in robot-assisted neurorehabilitation.